A interdisciplinaridade na formação dos profissionais de saúde no contexto da reabilitação - Gomes, Angely Caldas (2015)
The training of health professionals in an interdisciplinary perspective is considered a premise for a care reorganization model, aiming to reach teamwork and a more integral and resolutive approach of the human being, based on the principles and guidelines of Brazil’s Unified Public Health System (SUS). The aim of this study is to know the professional training in an interdisciplinary perspective of the following higher-degree courses: Physiotherapy, Speech Therapy, and Occupational Therapy. The study was held in João Pessoa – Paraíba, whose research was based on cross-sectional, exploratory, descriptive, and inferential model, developed from qualitative and quantitative approaches. The sample was composed by scholars enrolled in the last academic year of Physiotherapy, Speech Therapy, and Occupational Therapy higher-degree courses from two Higher Education Institutions (HEI’s) and also by Physiotherapists, Speech Therapists, and Occupational Therapists who compose the rehabilitation team from two specialized services of these HEI’s. For this purpose, the “Assessment of Training to Interdisciplinary” questionnaire adapted for rehabilitation context, aiming to know the profile of scholars and their position about approximations and distancing in training related to interdisciplinarity. For the qualitative phase with professionals, it was utilized a semi-structured interview guideline, aiming to analyze the facilitations and problems of an insertion in a rehabilitation team on professional practice scenario. The results of the questionnaires were submitted to Cluster Analysis by R statistical software; and the interviews’ content were organized and analyzed by Nvivo software, thus enabling the construction of Collective Subject’s Speech. Therefore, there were clear signs, in the higher-degree courses researched, limitations on the training in health professionals for interdisciplinarity, with the restriction of activities which contemplate and favor the join action of students, having a negative effect in professional practice. Professionals’ attitude facing the interdisciplinary actions highlighted the limitation in training, reflected on their difficulties, recognizing other professions’ duties and competencies within rehabilitation team. The discussion was utilized as strategy for overcoming in the search of interdisciplinarity achievement. The findings of this study evinced the changes in training process of future rehabilitation professionals, which requires planning and reorganization of academic practices in the perspective of interprofissional education.